Fidelity of Implementation in Assessment of Infants and Toddlers Evaluating Developmental Milestones and Outcomes - Stone-MacDonald, Angela (Springer International Publishing, 2018)
This book examines the challenges in developmental assessment of infants and toddlers and provides best practices for implementing standardized assessments in early intervention settings. It starts with an overview of standardized assessment practices and discusses how specific tools can be used in early intervention for different purposes (e.g., eligibility for services). The book explains the importance of the Fidelity of Implementation of Assessment (FOI-A) approach in creating standardized assessment for infants and toddlers. Chapters provide a checklist-based framework for FOI-A, with details on technological supports for test administration and data collection as well as training and supervision models. In addition, chapters discuss ways of engaging families, gaining their trust, and including them in their children's educational planning. Topics featured in this book include: The Battelle Development Inventory, 2nd Edition (BDI-2) and its use in the assessment of young children. Using checklists to improve fidelity of implementation for standardized assessments. Using checklists to support early intervention directors and teams. How to provide feedback to early interventionists and other professionals on FOI-A. Recommendations to improve FOI-A. Fidelity of Implementation in Assessment of Infants and Toddlers is a must-have resource for researchers, clinicians and related professionals, and graduate students in varied fields including child and school psychology, pediatrics, social work, behavioral therapy, infant and early childhood development, and early education and care.